FOURIER ANALYSIS APPLIED TO MIMOMYS (ARVICOLIDAE, RODENTIA, MAMMALIA) FIRST LOWER MOLARS - BIOCHRONOLOGICAL IMPLICATIONS - Marcolini F. (My University, 2006)
Fourier analysis was used in this study to help a specific determination of some Mimomys (Arvicolidae, Rodentia, Mammalia) species. Several Pliocene and Pleistocene Central and Western European Mimomys species first lower molar contours have been decomposed by Complex Discrete Fourier Transform. Inter- and intra-specific comparisons have been performed on the harmonics obtained from the decomposition and some problematic specimens have been classified. © Springer Science+Business Media, Inc. 2006.
Keywords: BIOCHRONOLOGY; MORPHOMETRY; PLIO-PLEISTOCENE; SMALL MAMMAL; Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен